Eternity, Relative Realities, and Ontological Idealism About Time - Moravec, Matyáš (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
This paper argues that idealism can offer a new solution to the problem of relating the “static” presence of things to eternity and the “dynamic” passage of reality in the temporal realm. I first offer a presentation of this problem using the dispute between Aquinas and Scotus, then describe “ontological idealism about time,” as a smaller–scale idealism, and show how it resolves the original problem. I conclude by demonstrating that this view is consonant with the recent emphasis on the ontological dependence of things on God and that it offers a way of bringing together non–eternalist ontologies and the ontological conclusions posited by the special theory of relativity.